1988
DOI: 10.1002/j.1460-2075.1988.tb02974.x
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of the regular surface glycoprotein layer of Halobacterium volcanii from the Dead Sea

Abstract: A three‐dimensional reconstruction from electron micrographs of negatively stained cell envelopes of Halobacterium volcanii has revealed the structure of the surface glycoprotein to a resolution of 2 nm. The glycoprotein is arranged on a p6 lattice with a lattice constant of 16.8 nm. It forms 4.5 nm high, dome‐shaped, morphological complexes with a narrow pore at the apex opening into a ‘funnel’ towards the cell membrane. The polarity of the structure was derived from freeze‐etching experiments and ‘edge’ view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 22 publications
7
57
0
Order By: Relevance
“…For example, iduronic acid, a major component of proteoglycans (296), is found in the glycans decorating the Halobacterium salinarum S-layer glycoprotein. Similarly, the O-glycosylation cluster situated near the membrane-spanning base of the Haloferax volcanii S-layer glycoprotein has also been assigned a structural support role in the formation of a periplasmic-like space (217). In Thermoplasma acidophilum, an organism that lacks a cell wall, it has been suggested that the glycan moieties attached to the major glycosylated membrane-bound protein species coating the cell surface act to either trap water molecules or allow the cell surface proteins to interact with each other.…”
Section: Role Of Protein Glycosylation In Archaeamentioning
confidence: 99%
“…For example, iduronic acid, a major component of proteoglycans (296), is found in the glycans decorating the Halobacterium salinarum S-layer glycoprotein. Similarly, the O-glycosylation cluster situated near the membrane-spanning base of the Haloferax volcanii S-layer glycoprotein has also been assigned a structural support role in the formation of a periplasmic-like space (217). In Thermoplasma acidophilum, an organism that lacks a cell wall, it has been suggested that the glycan moieties attached to the major glycosylated membrane-bound protein species coating the cell surface act to either trap water molecules or allow the cell surface proteins to interact with each other.…”
Section: Role Of Protein Glycosylation In Archaeamentioning
confidence: 99%
“…The main component of the cell wall is the S-layer formed by a hexagonal arrangement of a glycoprotein (25). A detailed structural study of the S-layer of H. volcanii (26) together with a a previous x-ray study of the envelope of H. halobium (27) led to a model in which the upper external part of the glycoprotein forms a dome-shaped region separated from the cell membrane by spacer elements (26). The protein is thought to be anchored in the plasma membrane by a hydrophobic stretch that is observed near the C terminus of both the H. halobium and H. volcanii glycoprotein sequence (28,29).…”
Section: Resultsmentioning
confidence: 99%
“…The protein is thought to be anchored in the plasma membrane by a hydrophobic stretch that is observed near the C terminus of both the H. halobium and H. volcanii glycoprotein sequence (28,29). The interspace between the plasma membrane and the external part of the S-layer has been considered as an aqueous space analogous to the periplasm of Gram-negative bacteria (26,27). However, if porins are present in the cell wall, but do not belong to the plasma membrane, they should be located in this interspace, which should then contain a lipid membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were obtained by Walker et al (1994), who proposed that the S-layer proteins of Caulobacter crescentus interact with lipopolysaccharide via calcium bridges. Finally, in the case of halobacteria, a short C-terminal hydrophobic sequence has been identified and proposed to be a cytoplasmic transmembrane anchoring sequence for the S-layer protein (Lechner and Sumper, 1987;Kessel et al, 1988;Sumper et al, 1990).…”
Section: Introductionmentioning
confidence: 99%